Bear and Dog Remains From an Agnevo River Sacred Site (Central Sakhalin). Issue 1 (3rd April 2019) - Gasilin, Viacheslav Vladimirovich; Gorbunov, Sergey Viacheslavovich
Abstract : The article compares data using archeo-zoological methods with ethnographic data for the first time. Brown bear and domestic dog bone mounds reveal rituals of the indigenous population of the Far East. Bear and dog bones uncovered on the central west coast of Sakhalin in front of a small grotto at the mouth of the Agnevo River establish the existence of a Nivkh sacred site. The disposal of the bones has permitted identification of the sacred site as belonging to the Ksyusvongun kin group. Traces on the bones have underscored distinctive kin group rites, distinguishing them from other Sakhalin Nivkh groups, and have indicated the possible influence of Amur Nivkh and island Ainu.